The price of inheritance : a novel - Tanabe, Karin (Washington Square Press, 2014)
"A world of big bucks deals and off-the-record promises, the high-end auction industry is a game of the elite. After eight years in the American Furniture department at Christie's, Carolyn Everett is a rising star. The 29-year-old has just sold the most expensive piece of American furniture ever made and four months later, acquires the country's premiere private furniture collection. But one wrong decision and a scandal that rocks Christie's leaves Carolyn unemployed and broken. Desperate to piece her life back together, she leaves New York City to work in a tiny antique store in Newport, Rhode Island. At a small county auction, she comes across a piece of Middle Eastern pottery, which she purchases for twenty dollars on a hunch. The journey to find its original owner takes her from beau monde Newport to the historic town's United States Navy Base and into a relationship with notorious womanizer Marine Sergeant Tyler Ford, who claims the relic was a gift from his translator during the early days of the Iraq War. Tyler and Carolyn, from two different worlds, fall into a relationship of mystery and obsession, until the provenance of the art that brought them together comes under intense scrutiny. Did Tyler participate in the raid of the National Museum of Iraq? Will he face criminal charges? And does Carolyn really know the man she's fallen in love with?"--